RESOLUTION OF LAND OWNERSHIP DISPUTES BETWEEN OWNERS OF OWNERSHIP CERTIFICATES AND OWNERS OF COMPENSATION DECLARATIONS (Study Decision Number: 78/Pdt.G/2023/PN Mdn) - Doly Amanda NST; Henry Aspan; Dina Andiza (RADJA PUBLIKA, 2025)
Land ownership disputes remain a frequent issue in Indonesia, particularly between owners of Land Ownership Certificates and those who control the land based on compensation letters. These differences in the basis of ownership and evidence of land ownership often give rise to legal conflicts that end up in court. This study aims to review a general overview of agrarian law in Indonesia, analyze the factors causing land ownership disputes between owners of Land Ownership Certificates and owners of compensation letters, and analyze the resolution of these disputes based on Medan District Court Decision Number 78/Pdt.G/2023/PN Mdn. The research method used is normative legal research with a statutory and case-based approach. Data sources used are primary, secondary, and tertiary legal materials analyzed qualitatively. The results indicate that land ownership disputes are influenced by disorderly land administration, low public legal awareness, overlapping land ownership, and differences in understanding between customary law and positive law. Medan District Court Decision Number 78/Pdt.G/2023/PN Mdn affirms that a Land Ownership Certificate is a strong and primary piece of evidence as long as it is issued in accordance with legal procedures and there is no evidence of administrative flaws. Therefore, land registration is a crucial instrument for ensuring legal certainty and protection of land rights.